Photoinduced Intervalence Charge Transfers: Spectroscopic Tools to Study Fundamental Phenomena and Applications. Issue 20 (3rd August 2022) - Ramírez‐Wierzbicki, Ivana; Cotic, Agustina; Cadranel, Alejandro
Abstract: The exploitation of excited state chemistry for solar energy conversion or photocatalysis has been continuously increasing, and the needs of a transition to a sustainable human development indicate this trend will continue. In this scenario, the study of mixed valence systems in the excited state offers a unique opportunity to explore excited state electron transfer reactivity, and, in a broader sense, excited state chemistry. This Concept article analyzes recent contributions in the field of photoinduced mixed valence systems, i. e . those where the mixed valence core is absent in the ground state but created upon light absorption. The focus is on the utilization of photoinduced intervalence charge transfer bands, detected via transient absorption spectroscopy, as key tools to study fundamental phenomena like donor/acceptor inversion, hole delocalization, coexistence of excited states and excited state nature, together with applications in molecular electronics. Abstract : Photoinduced intervalence charge transfers are excited‐state analogs of traditional intervalence charge transfers. They are simple models to study electron transfer and the shape of potential energy surfaces in the excited state. These transient absorption spectroscopic handles can be utilized in different (supra)molecular designs to acquire fundamental insights, resolve complex mechanisms, or reveal photoswitching behaviors.